If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -7j = -2j + 3 Reorder the terms: 6 + -7j = 3 + -2j Solving 6 + -7j = 3 + -2j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '2j' to each side of the equation. 6 + -7j + 2j = 3 + -2j + 2j Combine like terms: -7j + 2j = -5j 6 + -5j = 3 + -2j + 2j Combine like terms: -2j + 2j = 0 6 + -5j = 3 + 0 6 + -5j = 3 Add '-6' to each side of the equation. 6 + -6 + -5j = 3 + -6 Combine like terms: 6 + -6 = 0 0 + -5j = 3 + -6 -5j = 3 + -6 Combine like terms: 3 + -6 = -3 -5j = -3 Divide each side by '-5'. j = 0.6 Simplifying j = 0.6
| 4-3t=2t-20 | | 45x+9x=0 | | 43=7+y | | -4(4y-4)-y=-4(y-3) | | 7x^4-33x+26=0 | | 18(2-3)-2x=2x | | 6x+6=3(x+9) | | 2n+9=15 | | 4n+1=-23-2n | | g(x)=-f(-4) | | 3x-2y=-7 | | 6-7j=2j+3 | | 25W^2+10W+1=0 | | 5x+9=2(2x+3) | | -5x(4x-8y+4)= | | 3u+45=9(u+9) | | 2x^2+14x-144=0 | | -3x+5+6(x+1)=-2+3 | | 2(x+2)+4x=x+6 | | 9+c=-13 | | 4(s+2)-s=3(s+1) | | t=4n+4v | | 0.3(y+1)-0.4(3-2y)=0.2 | | 7x+5-4x-4=x | | (5cd^2)(-c^4d)= | | n^2+n+132=0 | | 2.5x+2.1=5.3 | | 5z^2-35=0 | | -4x^2+3x+10=0 | | 3u+45=9u+81 | | 3x-5=3(x+9) | | -3(x+1)+4x=13 |